INTERNALISASI NILAI HADIS TARBAWI TERHADAP TANGGUNG JAWAB SISWA DI SEKOLAH: Hadis tarbawi; Kejujuran; Kesadaran diri; Pembiasaan nilai; Tanggung jawab - Isnin Riskia Chaerani; lizah, siti Nurhalizah; Muhammad Hadzal Jibran; Muhammad Rendi Ramdhani (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2025)
Instilling responsibility in students is a crucial part of character education that cannot be developed instantly. This value needs to grow gradually through approaches that are closely connected to students’ daily school life. This study aims to explore how tarbawi hadiths can be integrated into school activities to foster a sense of responsibility among students. The research uses a library research method by reviewing various Islamic and educational literature. The findings show that values such as leadership, self-awareness, and honesty found in the hadiths serve as strong foundations for nurturing responsible behavior. When these values are applied in practical activities like classroom duties, self-reflection, and group discussions, students not only complete their tasks but also begin to understand the deeper meaning behind the roles they carry out. This study concludes that the internalization of tarbawi hadith values contributes significantly to the development of students’ personal and social responsibility. The implication is that schools should design learning experiences that support the natural growth of these values in students’ everyday lives.